Retirees’ Knowledge of Living in a Ventilated Apartment as a Measure for Healthy Ageing Promotion - Uchenna, Ugwu; Ogochukwu , Orji; Ezike, Amadi (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
Living apartment is an integral component of healthy ageing promotion particularly in old age. The present study aimed at determining the retirees’ knowledge of living in a ventilated apartment as a measure for healthy ageing promotion. The study was guided by three research questions and one null hypothesis. The normative survey research design was adopted for the study. A sample size of 80 respondents was purposively selected and used for the study. Data was generated through a researcher-designed questionnaire. Mean score, standard deviation and t-Test statistical tools were used for data analysis. The result showed that the retirees’ knowledge of the basic requirements and benefits of living in a ventilated apartment as a measure for healthy ageing promotion is high. The study also revealed that the female retirees’ knowledge on the benefits of living in a ventilated apartment as a measure for healthy ageing promotion is high while their male counterparts is low. Statistically, the study indicated significant difference between the male and female retirees’ knowledge on the benefits of living in a ventilated apartment as a measure for healthy ageing promotion at 0.05 level of significance. It was therefore concluded that the retirees possess adequate knowledge of living in a ventilated apartment as a measure for healthy ageing promotion. Efforts, therefore, should be directed towards knowledge sustainability and its applications